2016
DOI: 10.1590/1678-4324-2016150275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy Metals on Liver, Kidney, Gills and Muscles of Cyprinus carpio and Wallago attu inhabited in the Indus

Abstract: The present study was aimed to evaluate the effect of heavy metals on an important tissue of two fish species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 8 publications
4
13
0
Order By: Relevance
“…Our results are in agreement with and confirm reports from earlier findings that fish muscle generally accumulates lower concentrations of PTEs (except for Hg) than gills, liver and intestines [56,57]. Gills are the first target organ for exposure in fish [17,18] to PTEs in water which complex with mucus.…”
Section: The Distribution Of Ptes In Fish Tissuesupporting
confidence: 93%
“…Our results are in agreement with and confirm reports from earlier findings that fish muscle generally accumulates lower concentrations of PTEs (except for Hg) than gills, liver and intestines [56,57]. Gills are the first target organ for exposure in fish [17,18] to PTEs in water which complex with mucus.…”
Section: The Distribution Of Ptes In Fish Tissuesupporting
confidence: 93%
“…"The tissue samples were thawed at room temperature before analysis. Approximately 1 g (gills, liver, kidney and muscle) was weighed in an Erlenmeyer flask and digested with 5 ml Perchloric acid and 15 ml HNO3 on a hot plate until brown fumes ceased to evolve, then samples were cooled at room temperature, diluted with 50 ml distilled water by following [21]".…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Studies conducted on river Kabul revealed the presence of heavy metals in different fish species including Tor putitora, Ompok bimaculatus, Aorichthys seenghala, Cyprinus carpio, Labeo dyocheilus and Wallago attu in a higher concentration than the permissible limits [16][17][18]. Many recent studies reports the presence of heavy metals in various fish species from different parts of the country [19][20][21]. Keeping in view the current scenario of an increase in heavy metal concentrations in different freshwater bodies in Pakistan, and the increasing risks associated with consumption of fish having higher concentrations of toxic metals, the current study was carried out to determine concentrations of different heavy metals in the kidneys, liver, gills and muscle tissues of three highly consumed fish species (Garra gotyla, Cyprinus carpio and Cyprinion watsoni) from the river Panjkora, Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…There is noteworthy dissimilarity in the deposition of heavy metals in the visceral organs of the two fishes. Each metal is with tolerable level as mentioned by International authorities like World health organization, FAO and FEPA [18].…”
Section: Introductionmentioning
confidence: 99%